The Effect of Profitability, Solvency, Market Value, and Company Size on Stock Prices in Food and Beverage Sector Companies - Rifki Deva; Angguliyah Rizqi Amaliyah (Jurnal Bisnis Islam dan Kewirausahaan, 2022)
Stock prices on the Indonesia Stock Exchange (IDX) are not always fixed, stock price movements are very volatile, depending on the strength of demand and supply. The occurrence of stock price fluctuations in the capital market makes the stock market attractive to some investors. This study aims to determine how much influence the level of profitability, solvency, market ratios, and company size on stock prices. The research model used is descriptive statistical analysis and classical assumption test. The population of this study is the food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 - 2020 totaling 20 companies. The sample research method used purposive sampling technique with a total of 12 companies that met the criteria. Data analysis was performed using multiple linear regression. The results showed that partially the level of the profitability variable had an effect on stock prices with a probability of 0.00 which was smaller than the 0.05 significance level. The level of the solvency variable has no effect on stock prices with a probability of 0.184 which is greater than the 0.05 significance level. The market ratio variable has no effect on stock prices with a probability of 0.895 which is greater than 0.05. Meanwhile, the firm size variable has an effect on stock prices with a probability of 0.001 which is smaller than the significance level of 0.005. Simultaneously it can be concluded that the level of profitability, solvency, market ratio, and company size affect stock prices with a contribution of 51.8% in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2020. Keywords: Profitability, Solvency, Market Ratio, Firm Size, Stock Price